The influence of social media marketing activities on brand equity / Akmal Aini Othman, Siti Aishah Mohd Nor and Normah Ismail - Othman, Akmal Aini; Mohd Nor, Siti Aishah; Ismail, Normah (UiTM Cawangan Johor, 2019)
There are new ways which have been made available for companies and brands to market their products and services with the existence of social media. However, there is insufficient evidence on how the social media marketing activities may influence brand equity, particularly brand awareness, especially in Malaysia. This study is carried out in order to investigate the influence of social media marketing activities on brand awareness. It has adapted framework from previous research by classifying social media marketing activities as entertainment, customization, trendiness, and perceived risk. The questionnaires were distributed online through Facebook to 110 respondents who follow Company A’s social media page. The results indicate that all four independent variables significantly influence brand awareness.